'Pull' motivation: an activity-based typology of international visitors to New Zealand. Issue 2 (20th January 2019) - Fieger, Peter; Prayag, Girish; Bruwer, Johan
Abstract : Using the push and pull framework, this study examines the relationship between tourist activities in New Zealand and behaviours such as tourist spending, travel style (group vs. independent travel) and length of stay. Data from the International Visitor Survey were analysed for a 19-year period (1997–2015). The findings, based on 62, 288 respondents, identified 9 typologies of international visitors over this period. For example, type one visitors are primarily pulled by the nature-based activities offered in New Zealand while type two is pulled by adventure activities. Some of the typologies have activities that overlap reflecting the needs of international visitors. Significant relationships were found between the nine typologies, tourist spending, travel style and length of stay. Implications for destination marketing purposes are highlighted.